From no-confidence to nitric oxide acknowledgement: a story of bacterial nitric-oxide reductase - Koutný, M (Folia microbiologica, 2000)
The review briefly summarizes current knowledge of the bacterial nitric-oxide reductase (NOR). This membrane enzyme consists of two subunits, the smaller one contains haem C and the larger one two haems B and nonhaem iron. The protein sequence and structure of metal centres demonstrate the relationship of NOR to the family of terminal oxidases. The binuclear Fe-Fe reaction centre, consisting of antiferromagnetically coupled haem B and nonhaem iron, is analogous to Fe-Cu centre of terminal oxidases. The data on the structure and function of NOR and terminal oxidases suggest that all these enzymes are closely evolutionally related. The catalytic properties are determined most of all by the relatively high toxicity of nitric oxide as a substrate and the resulting strong need to maintain its concentration at nanomolar levels. A kinetic model of the action of the enzyme comprises substrate inhibition. NOR does not conserve the free energy of nitric oxide reduction because it does not work as a proton pump and, moreover, the protons coming into the reaction are taken from periplasm, i.e. they do not cross the membrane.
Keywords: Nitric Oxide; Bacteria; oxid dusnatý; Oxidoreductases; oxidoreduktasy